Impact of Er:YAG laser on wound healing following nonsurgical therapy: A pilot study - Kandice L. Klepper; Yong‐Hee Patricia Chun; David Cochran; Shuo Chen; Howard S. McGuff; Brian L. Mealey (Wiley, 2019)
Abstract The purpose is to examine early wound healing through histological analysis by characterizing connective tissue distribution and organization in the treated periodontium following nonsurgical therapy. Periodontal disease is a multifactorial pathological process that leads to the loss of the surrounding periodontium. Traditional periodontal therapies have proven beneficial in halting the progression of disease. The aim of this study is to investigate early wound healing in periodontal patients following hand/ultrasonic instrumentation alone, erbium‐doped yttrium aluminum garnet laser instrumentation alone, or a combination of hand/ultrasonic instrumentation and Er:YAG laser instrumentation for the nonsurgical treatment of periodontitis by histologic evaluation. Twenty‐one patients were randomized to receive nonsurgical therapy for the treatment of chronic periodontitis with three modalities prior to surgical therapy. Baseline clinical measurements were obtained prior to treatment. Wound healing was assessed by obtaining an otherwise discarded tissue sample following nonsurgical therapy of the selected study site. Samples were obtained at 2 or 6 weeks following initial therapy with a step‐back incision and fixated for histological and immunohistochemical analysis. There were minimal between‐group differences in the amount of collagen distribution when analyzing the Mallory-Heidenhain Azan trichrome, Picrosirus Red stain, and proliferating cell nuclear antigen at both time points. Descriptive analysis of baseline measurements showed no differences in probing depth change, bleeding on probing, and clinical attachment level following initial therapy between the three treatment groups at 2 or 6 weeks. Each treatment modality was effective in treating moderate to severe chronic periodontitis; however, the results of this study are inconclusive regarding superiority of any one treatment approach from a histologic and immunohistochemical perspective. Based on this assessment, there was increased fibroblast proliferation and collagen maturation between the 2‐ and 6‐week time point after treatment in all treatment groups, with few apparent differences between treatment groups. This pilot study qualitatively evaluated early wound healing in periodontal patients following non surgical therapy with various treatment modalities. When comparing descriptive outcomes of Er:YAG laser therapy and hand/ultrasonic instrumentation there were minimal differences in collagen distribution and density between groups. The evaluated modalities were each effective treating periodontal patients with non surgical therapy.